2021
DOI: 10.2196/26586
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Communication in Adults With and Without Moderate-to-Severe Traumatic Brain Injury: Survey of Social Media Use

Abstract: Background Individuals with a history of traumatic brain injury (TBI) report fewer social contacts, less social participation, and more social isolation than noninjured peers. Cognitive-communication disabilities may prevent individuals with TBI from accessing the opportunities for social connection afforded by computer-mediated communication, as individuals with TBI report lower overall usage of social media than noninjured peers and substantial challenges with accessibility and usability. Althoug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…The study of Brunner et al (2017) highlights that information and communication technologies are frequently used for individuals with TBI’s rehabilitation [ 18 ]. However, the current study shows that the resources available online for people with TBI are moderately accessible (accessibility score of 55%) which is consistent with the accessibility concerns reported the participants of Morrow et al (2021) study [ 4 ]. Morrow et al (2021) reported that accessibility, safety and usability remain important barriers for their use of online resources [ 4 ], reinforcing the importance of developing solutions to improve the accessibility of online resources.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The study of Brunner et al (2017) highlights that information and communication technologies are frequently used for individuals with TBI’s rehabilitation [ 18 ]. However, the current study shows that the resources available online for people with TBI are moderately accessible (accessibility score of 55%) which is consistent with the accessibility concerns reported the participants of Morrow et al (2021) study [ 4 ]. Morrow et al (2021) reported that accessibility, safety and usability remain important barriers for their use of online resources [ 4 ], reinforcing the importance of developing solutions to improve the accessibility of online resources.…”
Section: Discussionsupporting
confidence: 89%
“…Individuals with TBI have different use patterns for social media, videoconferencing platforms and general internet than non-injured individuals [ 4 ]. They need simplified content, visually accessible with low complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For individuals with TBI to benefit from social media use, it is critical to address the barriers they may encounter so we can provide solutions to overcoming those barriers. Studies to date have advanced our understanding of the needs and challenges of adults with TBI but are largely based on retrospective reflection (eg, via self-report surveys) or analysis of previous posts [29,[31][32][33]. Retrospective recall and self-reflection can be particularly challenging for adults with TBI, who commonly have impairments in declarative recall and metacognition [34,35], and analysis of posts does not illuminate the process of accessing social media in real time.…”
Section: This Studymentioning
confidence: 99%